Review of Criminology and Islamic Law on Perpetrators Child Abuse - Rafika Nursyahida; Noor Azizah (Istinbath : Jurnal Hukum, 2024)
This study examines cases of child abuse by biological parents as a form of domestic violence that requires serious legal intervention and protection of children's fundamental rights. The research aims to understand criminology and Islamic law perspectives on child abuse, identify the factors influencing its occurrence, and determine efforts to address child abuse within the framework of Islamic law. The method used is qualitative research with an empirical juridical approach. From a criminological standpoint, using the Psychogenesis theory, it is explained that criminal behavior is caused by various factors, including family conditions disrupted by divorce or parents being too busy with their careers, as well as the psychological factors of the perpetrators themselves. The results show that criminal behavior is a response to psychological issues arising from family conditions or personality pressures experienced by the perpetrators. Efforts through Islamic law emphasize the protection of children's rights as part of moral and sharia obligations, by strengthening moral and ethical values, upholding children's rights, and protecting children's rights as legal subjects.